Fate and transport of coastal driftwood: A critical review. (September 2021) - Murphy, Enda; Nistor, Ioan; Cornett, Andrew; Wilson, Jessica; Pilechi, Abolghasem
Abstract: Driftwood originating from natural and anthropogenic sources is abundant in coastal regions and plays an important role in ecosystems, providing habitat, structure, nutrients, and carbon storage. Conversely, large accumulations of driftwood can litter coastal zones, negatively impact coastal ecosystems and pose hazards to navigation, infrastructure and communities. Knowledge of the processes underlying the fate and transport of coastal driftwood is therefore needed to inform sustainable management practices. The present state of understanding is limited, and predominantly founded on studies of rivers and tsunamis, where the spatio-temporal scales and driving processes are significantly different from typical climatic or storm conditions in coastal waters. The authors critically review research on fate and transport of driftwood in coastal waters, and identify research needs and opportunities. Key knowledge gaps relate to: interactions between driftwood, littoral zone hydrodynamics and geomorphology; mechanisms of driftwood rafting and accumulation; and influence of weathering and degradation on mobility. Highlights: Driftwood from natural and anthropogenic sources is abundant in coastal zones Coastal driftwood provides habitat, structure, nutrients and carbon storage Negative impacts include hazards to navigation, infrastructure, and communities The state of knowledge surrounding coastal driftwood fate and transport is immature Knowledge gaps relate to driftwood supply and wood-hydrodynamics-shore interaction